Privatisasi: Implikasinya terhadap Perubahan Perilaku Karyawan dan Budaya Organisasi - Achmad Sobirin (Jurnal Siasat Bisnis, 2005)
Two variables are usually used as a basis to make decision of privatization. While this is not necessarily wrong, there in fact other factors that should be taken for consideration but so far being neglected. These are human and cultural factors. This paper discusses these two factors and hypothesizes their implications in the short term and long term. In the short term, it is hypothesized that privatization will create fear, anxiety, stress and dissatisfaction among employees in which their company being privatized but no significance implication to the organizational culture. In the long term it is hypothesized that these fear, anxiety, stress and dissatisfaction will gradually be re¬duced. Despite this expectation, in the long term it is also expected that the success of privatization will be de¬pending on the reaction of the people on the cultural change. Key Words: Privatisasi, perubahan organisasi, perilaku karyawan, budaya organisasi.